2020
DOI: 10.1111/aor.13843
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular assist device driveline infections in three contemporary devices

Abstract: Ventricular assist devices (VADs) are an established therapeutic option 1 for patients with end-stage heart failure and provide circulatory support until myocardial recovery, heart transplantation or as destination therapy. Over the last decade, mechanical circulatory support has further improved patient survival and quality of life due to improvements in the design and durability of the devices. 2 However, infection remains a major adverse event and a relevant cause of morbidity and mortality in VAD recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 23 publications
1
64
1
Order By: Relevance
“…32 Owing to biofilm on device material that cannot be easily removed/replaced, these infections often recur, requiring a variety of diagnostic and treatment measures, frequently combining conservative and surgical approach. 33,34 The most common organisms involved in DLIs are Grampositive skin flora such as Staphylococcus aureus (including methicillin-resistant S. aureus [MRSA]), coagulase-negative Staphylococci, causing > 50% of DLIs, 14,33,35 pyogenic Streptococci (e.g., Streptococcus pyogenes, Streptococcus agalactiae, etc. ), Coryneform bacteria, Enterococcus faecalis, Escherichia coli, Klebsiella sp., Proteus mirabilis, as well as Pseudomonas aeruginosa which is found in approximately 10 to 50% cases of DLI.…”
Section: Pathophysiology Of Vad-specific Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Owing to biofilm on device material that cannot be easily removed/replaced, these infections often recur, requiring a variety of diagnostic and treatment measures, frequently combining conservative and surgical approach. 33,34 The most common organisms involved in DLIs are Grampositive skin flora such as Staphylococcus aureus (including methicillin-resistant S. aureus [MRSA]), coagulase-negative Staphylococci, causing > 50% of DLIs, 14,33,35 pyogenic Streptococci (e.g., Streptococcus pyogenes, Streptococcus agalactiae, etc. ), Coryneform bacteria, Enterococcus faecalis, Escherichia coli, Klebsiella sp., Proteus mirabilis, as well as Pseudomonas aeruginosa which is found in approximately 10 to 50% cases of DLI.…”
Section: Pathophysiology Of Vad-specific Infectionmentioning
confidence: 99%
“…34 It is important to highlight trauma as a leading cause of DLI 13,28,29 necessitating suture anchoring DLES during the first 2 weeks, and after its removal adhesive anchoring devices for driveline immobilization. 14,29,33,56,66 Many centers of expertise in VAD implantation and management follow general cardiac surgery guidelines in perioperative prophylaxis using firstand second-generation cephalosporins (cefazoline or cefuroxime) for 24 to 48 hours covering Gram-positive and Gram-negative bacteria, 4,67 whereas antifungal prophylaxis is not a routine. 68 In patients allergic to β-lactams and/or cephalosporins, clindamycin or vancomycin is an acceptable alternative covering Grampositive pathogens.…”
Section: Prevention Measuresmentioning
confidence: 99%
“…Readmission for a driveline infection was evaluated according to the device type in one study. Those authors reported that patients with an HM 3 had a higher risk for driveline infection readmissions compared to those with an HW HVAD or an HM II [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of driveline infections in patients using octenidine was 11.8%; no infections were found in patients using a merbromin solution. In the study by Schlöglhofer et al [ 11 ], octenidine was used as a cleaning agent and the driveline infection frequency was reported to be 27.3%. Hozayen et al [ 18 ] reported a driveline infection frequency of 13% when soap and antimicrobial spray were used to clean the driveline exit site.…”
Section: Resultsmentioning
confidence: 99%
“…However, for LVAD pumps satisfying the engineering criteria does not completely serve the purpose. In fact, the LVAD pumps must be hemocompatible enough to minimize the post‐implant complications like bleeding, stroke, and infections 9‐14 . Furthermore, the technological aspects like compactness, bearing design, and biocompatibility are also very crucial for a successful LVAD pump.…”
Section: Introductionmentioning
confidence: 99%